¿Barreras lingüísticas en la educación?: la influencia de la lengua materna en la deserción escolar - Rodríguez, Efraín (2012)
Linguistic barriers in education?: the influence of the language in school desertionThe present work has as its objective to evaluate the effect of having a native language different than Spanish over the probability of abandoning basic schooling. For that purpose a proportional risk duration model (Cox) and an accelerated fail time model are used, using information from 2008 and 2009 ENAHO, as well as 2007 Censo Escolar. In both models we find a positive effect over the probability of leaving primary studies when having Quechua as a native language.  The results, for the case of the Quechua speakers, can show part of the effectiveness of the intercultural and bilingual education program (programa de Educación Intercultural Bilingüe or EIB in Spanish) for the reduction of inequality in the process of human capital accumulation